Analisis Pengaruh Kualitas Produk Harga Dan Lokasi Terhadap Keputusan Pembelian Pada Rumah Makan Bu Dewi Di Kalabahi Kec. Teluk Mutiara Kabupaten Alor - Ayub Asamani (Peneliti.net, 2023)
Purchasing decision is a process where consumers recognize the problem, seek information about a particular product or brand. This study aims to determine the effect of product quality, price, and location on purchasing decisions at Bu Dewi Restaurant, Kec. Teluk Mutiara, Alor Regency . The population in this study were all consumers who came to eat and drink at the Bu Dewi Restaurant, Kec. Teluk Mutiara, Alor Regency. While the sample in this research is accidental sampling . Data collection techniques used are observation techniques, interviews, questionnaires. The data were then analyzed using multiple linear regression analysis . The results of this study indicate that, (1). Partially Product Quality (X1) is 0.005, has a significant effect on Purchase Decision (Y) at Bu Dewi Restaurant, Kec. Teluk Mutiara, Alor Regency, with a (sig) Y value of 0.000. (2). Partially the price variable (X2) is 0.019, which has a significant effect on purchasing decisions (Y) at Bu Dewi's Restaurant, Kec. Teluk Mutiara, Alor Regency, with a (sig) Y value of 0.000. (3). Partially, the location variable (X3) is 0.028, which has a significant effect on purchasing decisions (Y) at Bu Dewi's Restaurant, Kec. Teluk Mutiara, Alor Regency, with a (sig) Y value of 0.000. (4). Simultaneously all variables (X) have a significant effect on purchasing decisions (Y) at Bu Dewi's Restaurant, Kec. Teluk Mutiara, Alor Regency, with a value (sig) of 0.000. Based on the results of the study, it is suggested that restaurant owners consider product supply, pricing, and location determination, so that purchasing decisions at Bu Dewi Kalabahi Restaurant, Alor Regency, automatically increase.